Liquid Crystals as Phase Change Materials for Thermal Stabilization - Eva Klemenčič; Mitja Slavinec (Advances in Condensed Matter Physics)
Thermal stabilization exploiting phase change materials (PCMs) is studied theoretically and numerically. Using the heat source approach in numerical simulations, we focus on phase change temperature as a key factor in improving thermal stabilization. Our focus is to analyze possible mechanisms to tune the phase change temperature. We use thermotropic liquid crystals (LCs) as PCMs in a demonstrative system. Using the Landau-de Gennes mesoscopic approach, we show that an external electric field or appropriate nanoparticles (NPs) dispersed in LCs can be exploited to manipulate the phase change temperature.